Development of Research-Based Learning IPAS E-Module Using the Book Creator Application in the Merdeka Curriculum - Estuhono Estuhono; Raimon Efendi (STAI Hubbulwathan Duri, 2024)
Students struggled to understand science learning content about the forms of substances and their changes due to the usage of printed teaching materials that only provided information in outline format. The research aims to develop a credible, practical, and effective e-module for scientific learners utilising a bookmaker application and research-based learning. The research and development (RD) approach is utilised. The Plomp model consists of three stages: preliminary study, prototype stage, and assessment phase, and is the development process used. The assessment portion of the research yielded an average of 88.7% in the highly valid category during the validity test. The homeroom teachers of classes I and IV found that the teacher response questionnaire research resulted in an average score of 82% in the highly practical category. The one-to-one evaluation experiment yielded an average of 92% in the highly practical category, while the small group evaluation trial achieved an average of 85% in the same area. The study of effectiveness data from three categories (knowledge, attitudes, and abilities) yielded an average of 81.36%, falling under the